Regulated bioanalysis : fundamentals and practice - Rocci, Mario L.; Lowes, Stephen (Springer, 2017)
This book is intended to cover the fundamental and practical aspects of regulated bioanalysis. The editors are seeking leading scientists in the field to participate in the development of this book, which we envision as a "one of a kind" contribution to our field. The book is intended for students in the pharmaceutical sciences, chemistry, biology and related scientific disciplines interested in bioanalysis, as well as working scientists new to the field of regulated bioanalysis. It will also serve as a primer for those experienced in the field. The depth of the book will seek to give its audience a solid foundation of knowledge in regulated bioanalysis which can be leveraged further with "hands on" experience. Understanding that bioanalytical global regulations evolve, the book is not intended as a deep-dive into regulatory language nuances but rather to be an educational text on conducting defendable and auditable science to support modern bioanalysis. Following an introduction to the topic by the editors, the book then covers "non-scientific" aspects of the topic area including the regulations governing this work, logistical and operational aspects of running a regulated bioanalytical laboratory and appropriate laboratory documentation. Next a description of the typically encountered types of bioanalytical samples, analytes and their attributes is provided. This information then sets the stage for a detailed discussion of the analytical platforms and assay types used in the regulated bioanalysis of small and large molecules. Also provided is a discussion of the different analytical phases of the bioanalytical process (i.e. method development including various strategies, pre-study validation and sample analysis).
Includes index.
Keywords: Drugs -- Analysis.; elektronické knihy; electronic books